Prognosis of idiopathic pulmonary fibrosis without anti-fibrotic therapy: a systematic review. (5th August 2020) - Khor, Yet H.; Ng, Yvonne; Barnes, Hayley; Goh, Nicole S.L.; McDonald, Christine F.; Holland, Anne E.
In addition to facilitating healthcare delivery planning, reliable information about prognosis is essential for treatment decisions in patients with idiopathic pulmonary fibrosis (IPF). This review aimed to evaluate the prognosis of patients with IPF without anti-fibrotic therapy. We included all cohort studies and the placebo arms of randomised controlled trials (RCTs) in IPF and follow-up of ≥12 months. Two reviewers independently evaluated studies for inclusion, assessed risk of bias and extracted data. A total of 154 cohort studies and 16 RCTs were included. The pooled proportions of mortality were 0.12 (95% CI 0.09–0.14) at 1–2 years, 0.38 (95% CI 0.34–0.42) between 2–5 years, and 0.69 (95% CI 0.59–0.78) at ≥5 years. The pooled mean overall survival was 4 years (95% CI 3.7–4.6) for studies with a follow-up duration of 10 years. At <2 years, forced vital capacity and diffusing capacity of the lung for carbon monoxide declined by a mean of 6.76% predicted (95% CI −8.92 −4.61) and 3% predicted (95% CI −5.14 −1.52), respectively. Although heterogeneity was high, subgroup analyses revealed lower pooled proportions of mortality at 1 year in the RCT participants (0.07 (95% CI 0.05–0.09)) versus cohort study participants (0.14 (95% CI 0.12–0.17)). This review provides comprehensive information on the prognosis of IPF, which can inform treatment discussions with patients and comparisons for future studies with new therapies. Without anti-fibrotic therapy, patients with IPF have a mortality rate of 31% at ≥5 years, and a mean overall survival of 4 years over 10 years of follow-up http://bit.ly/2SDiZSb